2014
DOI: 10.1177/0022034514554224
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Year Randomized Trial to Compare 1 or 2 Implants for Implant Overdentures

Abstract: The hypothesis of this 5-y randomized clinical trial was that there would be no significant difference in the satisfaction of edentulous participants with removable complete overdentures attached to 1 or 2 mandibular implants. Secondary aims were to test changes in satisfaction between and within the groups from baseline to 5 y and differences between the groups in implant survival and prosthodontic maintenance over 5 y. Each of the 86 participants (mean age, 67 y) was randomly allocated to receive either 1 im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
160
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(189 citation statements)
references
References 26 publications
8
160
4
1
Order By: Relevance
“…The selected nine studies 6,[27][28][29][30][31][32][33][34] were RCTs and were published between 1998 to 2016. The observation period ranged from 12 months to 10 years.…”
Section: Characteristics Of Included Studies:-mentioning
confidence: 99%
See 4 more Smart Citations
“…The selected nine studies 6,[27][28][29][30][31][32][33][34] were RCTs and were published between 1998 to 2016. The observation period ranged from 12 months to 10 years.…”
Section: Characteristics Of Included Studies:-mentioning
confidence: 99%
“…All of the studies were conducted in a university setting; four trials were conducted in Netherlands [27][28][29][30] , two studies in Canada 33,34 two studies in Egypt 31,32 and one in Germany 6 . Six studies reported delayed loading protocol [27][28][29][30][31][32] while the other three studies 6,33,34 followed an early/immediate loading protocol. In early loading protocol, the dentures were inserted 42 days after implant placement 33 whereas in immediate loading protocol the denture were inserted at time of surgical implant placement 1329 34 .…”
Section: Characteristics Of Included Studies:-mentioning
confidence: 99%
See 3 more Smart Citations